Does Light Touch Cluster Policy Work? Evaluating the Tech City Programme - Max Nathan (Institute of Labor Economics (IZA), 2019)
Despite academic scepticism, cluster policies remain popular with policymakers. This paper evaluates the causal impact of a flagship UK technology cluster programme. I build a simple framework and identify effects using difference-in-differences and synthetic controls on rich microdata. I further test for timing, cross-space variation, scaling and churn channels. The policy grew and densified the cluster, but has had more mixed effects on tech firm productivity. I also find most policy 'effects' began before rollout, raising questions about the programme's added value.
Keywords: L53; L86; O31; R30; R50; 330; cities; clusters; technology; economic development; synthetic controls